Uji Pratikalitas Pembuatan dan Perancangan Media Interaktif - Syukron Hamid Siregar; Yuliawati Yunus; Astri Indah Juwita (Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to determine the validity, practicality and effectiveness of Android-based interactive media creation and design in the subject of broad-based WAN (TEKWAN) Network Technology Class XI at SMK Negeri 6 Padang FY 2021/2022. This study uses research and development methods (Research & Development). The research subjects were 34 students of SMK Negeri 6 Padang. This research method uses analysis (ADDIE), with the design and development steps as follows. (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluate.The results of the overall practicality test assessment of the practicality assessment of Android-Based Interactive Media on the subject of Broad-Based Network Technology (WAN) Class XI at SMK Negeri 6 Padang is 92.21%, so the practicality level can be interpreted Very Practical to useIn conclusion, based on the assessment and expert input as well as the results of the field trial of Android-Based Interactive Media as a learning medium, it has been tested for feasibility, excellence, and can be used in the learning process on the subject of Broad-Based Network Technology (WAN) for class XI at SMK Negeri 6 Padang.